A escuta do espaço sonoro na obra de Cildo Meireles - Pinheiro, Elton Ribeiro (2016)
This research studies the listening to the sound space found in the work of Brazilian artist Cildo Meireles. In order to do that, it investigates the use of sound in the artist's work and its emission in six specific works, namely: Mebs/Caraxia (1970-71),